Effects of a 4-week combined sloped training program in young basketball players` physical performance - Figueira, B.; Gonçalves, B.; Abade, E.; Paulauskas, R.; Masiulis, N.; Sampaio, J. (Science & Sports, 2020)
Aim: The aim of this study was to compare the effects of a 4-week combined sloped training program with a standard flat training program performed by basketball players. Methods: A total of 31 male elite youth basketball players were randomly allocated into an experimental (SLOPE, n = 15, age 13.4 ± 0.4 y, height 168.8 ± 14.2 cm, weight 52.6 ± 12.7 kg) and control training group (FLAT, n = 16, age 12.9 ± 0.3 y, height 169.5 ± 9.3 cm, weight 56.2 ± 11.3 kg). A pre- to post-test design was used to explore the effects in performance variables. Results: The comparison between groups showed moderate higher values in FLAT training group for standing height jump (differences in groups means: % [90% confidence intervals], -10.2% [-14.9% to -5.3%]) and reaction time (5.8% [1.3% to 10.5%]). On the other hand, SLOPE training promoted a small improve in anaerobic-alactic power (W/kg) (3.4% [-1.2% to 8.1%]). The FLAT group presented small improvements in peak power (W), (-9.2% [-15.0% to -3.0%]) and moderate in relative peak power (W/kg) (-9.8% [-15.3% to -4.0%]). Power results suggested a more efficient movement pattern, probably due to a better propulsive phase supported by an improved ability to produce equivalent levels of force in a shorter period of time. Despite the identified benefits of combined uphill/downhill/flat training method, results suggest that young non-familiarize players need a progressive reduction of training load to optimize performance. These results represent important evidence into the planning guidelines of strength and conditioning coaches to support daily planning by choosing the most appropriate tasks to enhance players' performance.